Strategi Pengembangan Investasi Pasar Uang Syariah Pada Bank Syariah di Indonesia - Arief, Zaenal; Agus Taruno; Harisah; Rahmat Dahlan; Rahmawati (Universitas Muhammadiyah Jember, 2023)
The sharia money market at Sharia Commercial Banks in Indonesia is a forum for overcomes the liquidity shortage of financial institutions including sharia commercial banks as instruments with sharia principles. The research objective is to describe the BUS investment development strategy in PUAS which is a literature study with qualitative descriptive analysis. The result is there are two strategies, namely creating instruments and designing operational mechanisms.